The role of precision agriculture in food security. (5th December 2021) - Erickson, Bruce; Fausti, Scott W.
Abstract: Precision agriculture (PA) is the application of information technology to better manage crop and livestock production, heralded as another tool to advance food security around the world. Precision agriculture has the potential to increase productivity, improve resource allocation for inputs such as pesticides, fertilizers, water, feed, and labor, provide for more stable production, and reduce agricultural production's environmental effect. But PA is an approach that can be very different depending on farm characteristics, such as crops and livestock raised, farm size, management, the farms' access to technical support, and the characteristics of the operator such as age and education. As a result, the adoption of PA has been slower and less uniform compared with some other agricultural innovations. Modern PA management systems are rarely implemented on small low‐mechanization farms, which comprise much of the world's agricultural production, and these farms are common in areas of the world that are the least food secure. And like other farm technology, its benefits go primarily to its adopters and society as a whole, but those who do not, or cannot adopt are left at a relative disadvantage, which unfortunately at present are most farmers around the world. Food security's four main principles according to the Food and Agriculture Organization of the United Nations are food availability, access, utilization, and stability. Precision agriculture has an aspect unlike its predecessor innovations that were primarily production related–because it is based on information, it has the capacity also to better inform and to allow adjustment all along the food supply/demand chain. Core Ideas: Precision agriculture has a role in food security by helping with production efficiency and stability. The adoption of precision agriculture is more tied to farm and farmer characteristics than other technologies. Precision agriculture has not been widely adopted on smaller, nonmechanized farms, common where food is insecure. Information technology has the potential to inform beyond the farm to help with food security.